2022
DOI: 10.3390/s22072713
|View full text |Cite
|
Sign up to set email alerts
|

Ship Segmentation and Georeferencing from Static Oblique View Images

Abstract: Camera systems support the rapid assessment of ship traffic at ports, allowing for a better perspective of the maritime situation. However, optimal ship monitoring requires a level of automation that allows personnel to keep track of relevant variables in the maritime situation in an understandable and visualisable format. It therefore becomes important to have real-time recognition of ships present at the infrastructure, with their class and geographic position presented to the maritime situational awareness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Then, many parameters used on the score threshold filter the image, and these parameters become the output image and are displayed as segmented regions in the object. In marine situational awareness [33,34], YOLACT was used to recognize ships' classes and geographic locations in real-time from static oblique view images. The results showed that YOLACT had a faster FPS than DetectoRS, but a lower performance of overall mAP.…”
Section: Literature Reviewmentioning
confidence: 99%

Instance Segmentation Evaluation For Traffic Signs

Shi Heng Siow,
Abu Ubaidah Shamsudin,
Zubair Adil Soomro
et al. 2023
ARASET
“…Then, many parameters used on the score threshold filter the image, and these parameters become the output image and are displayed as segmented regions in the object. In marine situational awareness [33,34], YOLACT was used to recognize ships' classes and geographic locations in real-time from static oblique view images. The results showed that YOLACT had a faster FPS than DetectoRS, but a lower performance of overall mAP.…”
Section: Literature Reviewmentioning
confidence: 99%

Instance Segmentation Evaluation For Traffic Signs

Shi Heng Siow,
Abu Ubaidah Shamsudin,
Zubair Adil Soomro
et al. 2023
ARASET